All hands on deck navigating your team through crises, getting your organization unstuck, and emerging victorious - Boni, Peter J. (Recorded Books, 2016)
"Disruption creates ten times the opportunity to advance your organization and your career, according to former CEO and author Peter J. Boni. In ALL HANDS ON DECK: Navigating Your Team Through Crisis, Getting Your Organization Unstuck and Emerging Victorious, Boni shows any leader or aspiring leader exactly what to do. Following his advice, recognition and rewards come quickly. It allows leaders with or without an MBA or Ivy League education to leapfrog over those who have superior credentials or stronger ties to an old boys' network. Beginning with the riveting, true story of Massachusetts clipper ship Captain Josiah Nickerson Knowles who saved his crew and all but one passenger during not one but two shipwrecks in the Pacific, author Peter J. Boni demonstrates how adversity should be embraced, rather than avoided. Boni presents a proven process to overcome chaos and disorder. By interviewing himself as the CEO of embattled Safeguard Scientifics as well as five prominent C-suite executives who triumphed over difficulties in the fields of consumer products, healthcare, biotech, non-profit and academia, we understand the thinking and actions necessary to get and keep organizations out of trouble and onto solid ground. The 12-Step Kedge-Off Process that Boni created is a blueprint for repositioning organizations and a model for any executive facing business dysfunctions and setbacks. The Process is divided into three phases, each anchored with the easy to remember moniker the ""ABCs to Advance:"" Boni would agree that you cannot prevent the storms that are inevitable in real life situations. But with his ABCs to Advance as well as the instructive real life stories of ALL HANDS ON DECK, we have a valuable guide for how to think in a crisis and how to cultivate the character traits to become an effective leader. While the techniques will get you out of a jam, use them early enough and they may very well KEEP you out of a jam."
Downloadable audio file
Keywords: Business; Affaires; BUSINESS & ECONOMICS; General; Downloadable audio books; Audiobooks; Livres audio